Prevalence of Vitamin D3 deficiency among pediatric patients with idiopathic nephrotic syndrome in remission - A cross-sectional observational study from Vadodara, Gujarat - Solanki, Jayesh R; Sudhakaran, Shruthy; Shringarpure, Kalpita S (Indian Journal of Child Health, 2018)
Background: Vitamin D deficiency occurs in nephrotic syndrome (NS) through various mechanisms, resulting in loss of both, Vitamin D binding protein and 25-(OH) D, in the urine leading to the risk of bone disorders. Objectives: The objectives of the study were to detect the prevalence of Vitamin D deficiency in children with idiopathic NS during remission. Methods: This study was conducted from April to November 2016 at the pediatric nephrology clinic at a tertiary care hospital in Vadodara. A total of 34 children were enrolled with idiopathic NS in remission, of which 14 had first attack of NS and ten of Frequently Relapsing Nephrotic Syndrome (FRNS) and Infrequently Relapsing Nephrotic Syndrome each. Vitamin D levels were measured using serum levels of 25-(OH) D by chemiluminescence method. Results: Vitamin D deficiency was observed in 28 of 34 (82%) children; of which, 16 (47%) had severe deficiency and 12 (35.2%) had mild to moderate deficiency. Children with the first attack of NS had a median Vitamin D level of 8.17 ng/ml (interquartile range [IQR] 2.9–28), IFRNS had a median of 6.8 ng/ml (IQR 2.9–33), and FRNS had the lowest median of 5.3 ng/ml (IQR 2.9–16). Although there were differences among all the 3 groups, differences were not statistically significant (Kruskal–Wallis 4.89, p=0.08) which showed decreased levels of Vitamin D. Conclusion: High prevalence of Vitamin D deficiency was observed in all 3 groups of idiopathic NS; the lowest being in FRNS. There was no significant association with lower levels of Vitamin D and relapses in NS. More research is needed to assess Vitamin D deficiency and to ensure the effect of Vitamin D supplementation for children with NS.